Buckwheat, quinoa and amaranth: Good alternatives to nutritious food - Škrobot Dubravka; Milovanović Ivan; Jovanov Pavle; Pestorić Mladenka; Tomić Jelena; Mandić Anamarija (Journal on Processing and Energy in Agriculture, 2019)
The purpose of this paper is to characterize the amino acid profiles of wholegrain buckwheat, quinoa and amaranth proteins. The content and protein quality of these pseudocereals were compared mutually and with those of wholegrain wheat as a widespread cereal in human nutrition. Amaranth seeds showed the highest total amino acid (TAA) content, followed by wholegrain buckwheat and quinoa, which showed the lowest TAA content compared to the other two pseudocereals (180.85, 162.46 and 125.37 g per 100 g protein, respectively). The protein digestibility, protein efficiency ratio, protein chemical score and essential amino acid index of the pseudocereals under consideration ranged from 79.25 - 84.58 %, 2.9 - 6.17 %, 16.24 - 47.59, and 45.68 - 68.36, respectively. The results obtained indicate that buckwheat, quinoa and amaranth are promising raw materials that can meet the daily requirements of most essential amino acids, and can be used for the development of a range of value-added bakery products.